IMPLEMENTASI STRATEGI PEMASARAN DALAM MEDIA PROMOSI SPMB DI MTS ZIA SALSABILA KABUPATEN DELI SERDANG - Muhammad Ilham; Nurhadida Nasution (Smart Education, 2026)
Abstract: The success of increasing the number of new student enrollments is greatly influenced by the implementation of effective and well-planned marketing strategies. This study aims to analyze the marketing strategies implemented by the Promotion and New Student Admission System (SPMB) unit at MTs Zia Salsabila. Using a case study approach, this research focuses on examining the implementation of marketing strategies in school promotional activities as well as the execution of the new student admission process. This study found that promotional strategies implemented through social media, supported by the dissemination of educational content and collaboration with elementary schools, have a significant impact on increasing prospective students' interest and the number of applicants to educational institutions. In addition, the application of digital-based marketing strategies has proven effective in expanding outreach to students. The study recommends continuous evaluation of marketing strategies to ensure they remain aligned with current trends and the needs of students, thereby optimizing the institution’s attractiveness in recruiting applicants. Keywords: Digital Marketing, Marketing Strategy, Promotional Media, Madrasah, Education Abstrak: Keberhasilan peningkatan jumlah peserta didik baru sangat dipengaruhi oleh penerapan strategi pemasaran yang efektif dan terencana. Penelitian ini bertujuan untuk menganalisis strategi pemasaran yang diterapkan oleh unit Promosi dan Sistem Penerimaan Murid Baru (SPMB) di MTs Zia Salsabila. Dengan menggunakan metode studi kasus, penelitian ini berfokus pada pengkajian implementasi strategi pemasaran dalam kegiatan promosi sekolah serta pelaksanaan proses penerimaan peserta didik baru. Penelitian ini menemukan bahwa strategi promosi melalui media sosial, didukung oleh penyebaran konten edukatif serta kerja sama dengan Sekolah Dasar, memberikan dampak yang signifikan dalam meningkatkan minat dan jumlah pendaftar pada lembaga pendidikan.Di samping itu, penerapan strategi pemasaran berbasis digital terbukti efektif dalam memperluas jangkauan kepada calon murid. Penelitian ini merekomendasikan pentingnya evaluasi secara berkelanjutan terhadap strategi pemasaran agar tetap relevan dengan perkembangan tren dan kebutuhan calon murid, sehingga mampu mengoptimalkan daya tarik institusi dalam menjaring pendaftar. Kata Kunci: Digital Marketing, Strategi Pemasaran, Media Promosi, Madrasah, Pendidikan